Alien agenda : investigating the extraterrestrial presence among us - Marrs, Jim. (New York : Harper Collins Publishers, 1997)
"Author and award-winning Journalist Jim Marrs has uncovered compelling new evidence regarding extraterrestrials-that alien life forms have not only visited our planet in the past, but are among us right now. Drawing on numerous eyewitness accounts, highly classified CIA reports, and his own meticulous research, Marrs marshals an impressive array of facts to confirm the reality of UFOs--as well as the depth of the government campaign to keep America in the dark. Here is information unavailable in any other single source, including: intriguing insights into the 1947 Roswell crash and the U.S. military's efforts to suppress all public inquiries, detailed accounts of UFO landing sites in South America and of abductions in the U.S., vivid descriptions of UFOs by Apollo astronauts-in their own words, tantalizing clues to the alien timetable for revealing their plans here, And much more!"--Book cover
Includes bibliographical references (p. [395]-425) and index.
Keywords: Unidentified flying objects -- Sightings and encounters; Life on other planets; Human-alien encounters